The Size and Incidence of the Losses from Noise Trading - DE LONG, J. BRADFORD; SHLEIFER, ANDREI; SUMMERS, LAWRENCE H.; WALDMANN, ROBERT J. (Journal of Finance, 1989)
ABSTRACT Recent empirical research has identified a significant amount of volatility in stock prices that cannot easily be explained by changes in fundamentals; one interpretation is that asset prices respond not only to news but also to irrational “noise trading.” We assess the welfare effects and incidence of such noice trading using an overlapping‐generations model that gives investors short horizons. We find that the additional risk generated by noise trading can reduce the capital stock and consumption of the economy, and we show that part of that cost may be borne by rational investors. We conclude that the welfare costs of noise trading may be large if the magnitude of noise in aggregate stock prices is as large as suggested by some of the recent empirical litrature on the excess volatility of the market.